Spatial pattern and decomposition analysis of the place of residence and sexual violence among women with disabilities in sub-Saharan Africa - Obasanjo Afolabi Bolarinwa; Clifford Odimegwu; Aliu Mohammed; Ezra Gayawan; Million Phiri (Discover Social Science and Health)
Abstract Background Sexual violence against women is highly pervasive worldwide and remains a major public health concern. Despite the global efforts to eliminate all forms of violence against women, recent estimates revealed that approximately 1 in 3 women have experienced physical or sexual violence in their lifetime, and women with disabilities have the greatest risk of sexual violence, particularly in Africa. Thus, this study investigates the spatial pattern and decomposition analysis of the place of residence and sexual violence among women with disabilities in sub-Saharan Africa. Methods We used the most recent secondary data from demographic health surveys, including a disability module, conducted between 2013 and 2022 in 10 sub-Saharan African countries. The study sample comprised 16,517 women with disabilities. Spatial analysis was applied to identify patterns of sexual violence, and a multivariable Blinder-Oaxaca decomposition regression analysis was used to explore the disparities between place of residence and sexual violence. The analysis took into consideration the complex survey design, with results reported in terms of percentages and adjusted coefficients. Results The spatial pattern of sexual violence among women with disabilities varies significantly across the sub-Saharan African countries included in the study, with prevalence rates ranging from 10 to 80%. The Democratic Republic of Congo reported the highest prevalence at 23%, while Mauritania reported 2%. No cases of sexual violence were reported in Nigeria and Chad. The analysis shows that the majority of the disparity in sexual violence (72.81%) is due to differences in characteristics, with 27.19% attributed to differences in coefficients. Overall, 79.77% of women with disabilities residing in rural areas reported experiencing sexual violence. Finally, the multivariable logistics regression shows that women with disabilities who were exposed to mass media exposure were associated with lower odds of experiencing sexual violence in urban areas [aOR = 0.69*; 95%(CI 0.49–0.97), p < 0.05] but with higher odds in rural areas [aOR = 1.26**; 95%(CI 1.08–1.47), p < 0.01]. Conclusions and recommendations The study reveals that women with disabilities in sub-Saharan Africa are vulnerable to sexual violence in both rural and urban areas, with a particularly high prevalence in rural regions. These findings are crucial for guiding the design and implementation of targeted interventions to combat sexual violence in the region.